Modeling tropical cyclone risk while accounting for climate change and natural infrastructure in the Caribbean - Borja G. Reguero; Pelayo Menéndez Fernández; Allison Bailey; Katie Arkema; Roberto Guerrero Compeán (Inter-American Development Bank (IDB), 2023)
This chapter describes tools and a methodology to model wind and flood risks from tropical storms under present and future climate accounting for natural infrastructure. Wind forcing provide a crucial link to hydrodynamic models that can be used in risk assessments to estimate extent of and damages from flooding and erosion. Further, such flood risk models can then include the effects of ecosystems, such as mangroves, to model the effects on risk of conservation and restoration outcomes but also individual nature-based projects to reduce risks. The chapter describes hazard modeling techniques and presents simple applications to (1) assess the effect of climate change in the Caribbean, by estimating wind fields for tropical cyclones for present and future climate scenarios, (2) address the limited observations in hurricane data by using existing tools to derive synthetic storms and readily use them in coastal models, and (3) compare modeling approaches and datasetsto provide recommendations for assessing flood attenuation of mangroves. The results and data developed in these applications is available with this chapter to be used in other local applications, or to infer damages from wind or in flood hazard models.
Keywords: C63; Q20; Q54; 330; Disaster risk assessment; tropical cyclones; flood hazard modeling; mangroves